Polypropylene carbonate biodegradable composite film and preparation method thereof

By introducing nanochitosan and nanofibrilose into PPC and working in concert with essential oils, the problems of low strength, poor dimensional stability and lack of antibacterial properties of PPC materials are solved, and a high-performance PPC/NCS/NFC composite film is achieved, which is suitable for food packaging and other fields.

CN119875340AActive Publication Date: 2025-04-25NINGBO UNIV

Patent Information

Application Number
CN202410423697.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-09
Publication Date
2025-04-25
Estimated Expiration
2044-04-09

AI Technical Summary

Technical Problem

The existing PPC materials have low strength, poor dimensional stability and lack of antibacterial properties, making it difficult to meet the application needs in food packaging and other fields.

Method used

PPC/NCS/NFC composite film is used to improve the mechanical properties, dimensional stability and antibacterial properties of the film by introducing nanochitosan (NCS) and nanofibrilose (NFC) into PPC and synergistically with essential oils.

Benefits of technology

It significantly improves the tensile strength and elastic modulus of PPC composite film, enhances dimensional stability, and imparts good antibacterial performance, meeting the application needs in food packaging and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875340A_ABST
    Figure CN119875340A_ABST
Patent Text Reader

Abstract

The invention discloses a polypropylene carbonate (PPC) / nano chitosan (NCS) / nano cellulose (NFC) biodegradable antibacterial composite film which comprises the following components in parts by mass: 100 parts of PPC, 1-10 parts of NCS, 1-14 parts of NFC, 1-10 parts of essential oil, 0.5-1 part of a lubricant, 0.5-1 part of a stabilizer and 0.5-1 part of a surfactant. According to the invention, one-pot preparation of the NCS and the NFC is realized, and the process is simple, convenient and efficient. Compared with a pure PPC material, NFC in the composite material serves as a reinforcing phase, NCS serves as an antibacterial phase, the mechanical property of PPC can be improved, and the PPC is endowed with good antibacterial performance. In addition, the essential oil is added, so that the synergistic effect of the NCS and the essential oil is initiated, and the antibacterial property of the film is further improved. The preparation method disclosed by the invention is simple, efficient, low in cost, low in equipment requirement, small in auxiliary agent dosage and easy to realize industrial production, and has a wide market application prospect and commercial value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of degradable plastic composite films, and in particular is a polypropylene carbonate / nano-chitosan / nano-cellulose biodegradable antibacterial composite film and a preparation method thereof. Background Art

[0002] Polypropylene carbonate (PPC) is a highly tough biodegradable polyester polymerized by polymerization of propylene oxide and carbon dioxide (CO2). PPC has the characteristics of biodegradability and biocompatibility, and can effectively reduce the greenhouse effect and reduce dependence on fossil resources, so it has received more and more attention. This material shows significant application potential in the fields of packaging films, textile fibers, electronic packaging, etc. However, due to its low relative strength, insufficient dimensional stability and lack of antibacterial ability, it has no advantages in the fields of food packaging. Therefore, it is urgent to improve the mechanical properties, dimensional stability, and give it antibacterial ability without affecting the toughness and biodegradability of PPC composites.

[0003] Nanofibrillated cellulose (NFC) is a new type of cellulose derivative with a unique structure, large surface area and a wide range of sources. It can be used as a low-cost nanofiller to strengthen and toughen polymer composites. NFC-reinforced composites have the advantages of biocompatibility and excellent mechanical properties, wear resistance and biodegradability. For example, Hu et al. (Compos. Sci. Technol. 2013, 78: 63-68) used 0.1wt% of NFC as a reinforcing material to prepare a PPC composite material and found that its tensile strength and Young's modulus increased to 19MPa and 1414MPa, respectively, the tensile strength increased by 10 times, and the Young's modulus increased by 7 times. Guo et al. (Polym. Adv. Technol. 2020, 31 (4): 853-863) found that the tensile strength of the PPC composite material increased with the increase of NFC addition. When the NFC addition amount increased to 1wt%, the tensile strength of the composite material increased from 22.1MPa to 29.8MPa. Introducing NFC into PPC can not only achieve mechanical strengthening, but also significantly improve the shape and dimensional stability of PPC. However, Tian et al. (Polym. Adv. Technol. 2020, 31 (11): 2408-2421) pointed out that due to the influence of various factors such as microorganisms and oxygen, there are many limitations in the storage and preservation of food. The antibacterial properties of PPC reinforced films need to be strengthened, and currently they still cannot meet the requirements for improving food safety and shelf life.

[0004] Adding chitosan (CS) is an effective way to impart antibacterial properties to PPC / NFC composites without affecting their mechanical properties and dimensional stability. CS is a product of partial removal of acetyl groups from the natural polysaccharide chitin, and has multiple physiological functions such as biodegradability, biocompatibility, non-toxicity and antibacterial properties. It has high antibacterial activity against a variety of pathogenic microorganisms and spoilage microorganisms (including fungi, Gram-positive bacteria and Gram-negative bacteria). Quan et al. (RSCAdv.2021, 11:10121-10129) reported that PPC / CS composites showed high antibacterial activity against Escherichia coli and Staphylococcus aureus. In addition, reducing the size of chitosan particles at the nanoscale, namely nanochitosan (NCS), can increase the specific surface area and improve antibacterial activity. The molecular structure of NCS can promote the interaction between NFC and PPC molecules. These interactions may involve hydrogen bonds, van der Waals forces and mechanical interlocking, which help to enhance plasticity, fluidity and mechanical properties. Murugesan et al. (Processes. 2020, 8(9): 1173) showed that NCS and its derivatives are one of the better nanomaterials that provide antibacterial activity. However, due to the hydrophilic nature of CS, its water vapor permeability (WVP) is high, which is not conducive to the preparation of thin films. To solve this problem, hydrophobic materials such as lipids, such as essential oils, are usually added to CS. Essential oils can improve the antibacterial activity of NCS. They have a synergistic effect in antibacterial properties. When essential oils are loaded on NCS nanostructures, the antibacterial activity is enhanced. Therefore, the present invention proposes a convenient preparation method of NFC and NCS, and develops a fully biodegradable composite film based on PPC. NFC is used to improve the mechanical properties and dimensional stability of the PPC composite film, and the antibacterial properties of the film are further improved by inducing the synergistic effect of NCS and essential oils. Summary of the invention

[0005] The problem to be solved by the present invention is that, in view of the problems of low strength, poor dimensional stability and lack of antibacterial property of existing PPC materials, a PPC / NCS / NFC high-performance biodegradable composite film and a preparation method thereof are proposed.

[0006] The technical solution adopted by the present invention to solve the above technical problems is: a PPC / NCS / NFC composite film, whose mass parts are as follows: 100 parts of PPC, 1-10 parts of NCS, 1-14 parts of NFC, 1-10 parts of essential oil, 0.5-1 part of lubricant, 0.5-1 part of stabilizer, and 0.5-1 part of surfactant.

[0007] Preferably, the NFC source is one or a combination of two or more of wood powder, bamboo powder, corn straw powder, rice straw powder and cotton stalk powder in biomass powder.

[0008] Preferably, the essential oil is one or a combination of two or more of orange peel essential oil, wormwood essential oil, cinnamon essential oil and hyssop essential oil.

[0009] Preferably, the lubricant is one or a combination of two or more of stearic acid, ethylene bis stearamide, oleamide, and erucic acid amide. Preferably, the stabilizer is one or a combination of two or more of antioxidant 1010, antioxidant 168, antioxidant 1076, and antioxidant 1790, and the surfactant is one or a combination of two or more of Tween-80, Tween-85, mannitol erythritol lipid-a, and mannitol erythritol lipid-b.

[0010] The above-mentioned method for preparing a PPC / NCS / NFC composite film comprises the following steps:

[0011] 1. One-pot preparation of NFC and NCS

[0012] 1) 10 to 30 parts of biomass powder are mixed with 70 to 90 parts of sodium hydroxide solution, stirred in a water bath at 75° C. for 6 hours, filtered after the reaction is completed, washed the solid sample obtained by filtration until neutral, added with a mixed solution of 80 to 90 parts of sodium chlorite solution and 4 to 5 parts of glacial acetic acid, heated and stirred at 70 to 80° C. for 1 to 2 hours, then washed with pure water until neutral, and dried to absolute dryness;

[0013] 2) 1 to 14 portions of the dried sample obtained in 1) and 1 to 10 portions of CS are placed in a container, pure water is added to adjust the solid-liquid ratio to 1:10 to 1:20, and then the solid-liquid mixture is placed in a homogenizer for high-speed shearing at a speed of 10,000 to 18,000 rpm for 0.5 to 2 hours. Finally, a centrifuge with a speed of 10,000 to 15,000 rpm is used for centrifugation for 3 to 5 minutes, and a mixed powder of NFC and NCS is obtained after freeze drying.

[0014] Preferably, in step 1), the mesh size of the biomass powder is 80-150 meshes, the concentration of the sodium hydroxide solution is 10-20 wt %, and the concentration of the sodium chlorite solution is 10-15 wt %.

[0015] Reducing the size of CS at the nanoscale can improve the antibacterial activity. In the present invention, the solute sample obtained in 1) and CS are made into nanoscale mixed particles by high-speed shearing in step 2) of the above method, thereby increasing the specific surface area of ​​both. In addition, the molecular structure of CS is very similar to that of cellulose, and only the functional groups connected to the second carbon in the repeating unit are different from each other. This method can make the two phases uniformly pre-dispersed, so NFC and NCS have good compatibility, which is conducive to uniformly blending the two in PPC. In the present invention, the one-pot preparation of NFC and NCS is achieved in step 2) of the above method, and the process is simple and efficient.

[0016] 2. Preparation of PPC / NCS / NFC composite film

[0017] a: First, add 1 to 10 parts of essential oil to the mixed powder of NFC and NCS obtained in step 2), then add 0.5 to 1 part of surfactant, blend in a high-speed mixer for 20 to 40 minutes, then add 100 parts of PPC, 0.5 to 1 part of lubricant, and 0.5 to 1 part of stabilizer and continue blending for 30 to 60 minutes.

[0018] b: melt-extrude the mixture obtained in step a in a twin-screw extruder for granulation at a temperature of 110 to 180° C. and a screw speed of 60 to 200 rpm to obtain PPC / NCS / NFC composite particles;

[0019] c: Processing the composite particles obtained in step b into a PPC / NCS / NFC composite film using a flat vulcanizer, a blown film machine or a cast film machine.

[0020] Preferably, in step c, the pre-pressing pressure of the flat vulcanizing press is 0.5-0.7 MPa, the pre-pressing time is 150-180 s, the pressing pressure is 2.5-3.5 MPa, the pressing time is 150-180 s, and the hot pressing temperature is 140-150°C.

[0021] Preferably, the processing temperature of the film blowing machine in step c is 120-160°C.

[0022] Preferably, the processing temperature of the cast film machine in step c is 120-160°C.

[0023] Preferably, the thickness of the PPC / NCS / NFC composite film in step c is 0.05 mm to 0.8 mm.

[0024] In the method of the present invention, NFC and NCS are fully mixed with essential oil in step a, thereby improving the synergistic antibacterial effect of NCS and essential oil; meanwhile, step a can also preliminarily improve the dispersibility of NFC, NCS and PPC, strengthen the homogeneous combination of two nanophases of NFC and NCS and PPC during the melt processing, and reduce the agglomeration phenomenon.

[0025] The method of the present invention realizes the interfacial entanglement between NFC and PPC molecular chains through step a. Since NFC has high strength and rigidity, this is the main reason for strengthening the PPC composite film. In addition, functional groups such as amino and hydroxyl groups on NCS show a certain plasticizing effect, which can improve the rheological properties of PPC and enhance the interfacial interaction between NFC and PPC. This enhanced interfacial interaction reduces the initiation and expansion of cracks, thereby improving the overall strength and toughness of the composite material.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] 1. The present invention adopts a one-step preparation method, and realizes the preparation of NCS while preparing NFC, and the process is simple and efficient. In addition, compared with pure PPC materials, NFC as a reinforcing phase and NCS as an antibacterial phase in the composite material can improve the mechanical properties of PPC and impart good antibacterial properties; compared with adding NFC and NCS to PPC, the method of the present invention can make NFC and NCS more easily dispersed in PPC, thereby improving the mechanical properties of PPC.

[0028] 2. The present invention improves the antibacterial activity of NCS through the synergistic effect of NCS and essential oil, so that the PPC / NCS / NFC composite film has more excellent antibacterial properties. NCS has a positive charge and can produce electrostatic interaction with negatively charged essential oils during high mixing, so that the two have a synergistic effect in antibacterial. In addition, essential oils are hydrophobic, and adding them to NCS can effectively reduce its water vapor permeability, which is beneficial to the preparation of the film.

[0029] 3. Compared with the preparation method of the traditional PPC composite film, the method of the present invention is easy to process, has low equipment requirements, and uses less additives. In the present invention, NFC and the PPC matrix form a mechanical strengthening effect, and the unique network structure of NFC locks the molecular chains of PPC, thereby hindering their sliding and effectively improving the dimensional stability of the PPC matrix. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 : Tensile properties of PPC / NCS / NFC composite films with different NFC addition amounts;

[0031] Figure 2 : SEM images of PPC / NCS / NFC composite films with different NFC addition amounts (a: Example 1; b: Example 2; c: Example 3; d: Example 4; e: Example 5);

[0032] Figure 3 :Dimensional stability of PPC / NCS / NFC composite films with different NFC addition amounts;

[0033] Figure 4 : Antibacterial activity of PPC / NCS / NFC composite films with different NCS addition amounts against Escherichia coli;

[0034] Figure 5 : Antibacterial properties of PPC / NCS / NFC composite films with different NCS addition amounts against Staphylococcus aureus;

[0035] Figure 6 : Antibacterial activity of PPC / NCS / NFC composite films with different essential oil addition amounts against Escherichia coli;

[0036] Figure 7 : Antibacterial properties of PPC / NCS / NFC composite films with different essential oil addition amounts against Staphylococcus aureus;

[0037] Figure 8 : Tensile properties of PPC / NCS / NFC composite films with different shear treatment times;

[0038] Fig. 9 : SEM images of PPC / NCS / NFC composite films with different shear treatment times (a: Example 16; b: Example 17);

[0039] Fig.10 : Tensile properties of PPC / NCS / NFC composite films at different shear treatment speeds. DETAILED DESCRIPTION

[0040] The present invention is further described in detail below with reference to the accompanying drawings.

[0041] The mass fraction compositions of the PPC / NCS / NFC composite films of Examples 1 to 5 are shown in Table 1, and the PPC / NCS / NFC composite films of Examples 1 to 5 are numbered C1, C2, C3, C4, and C5, respectively, for single factor experiments.

[0042] In Examples 1 to 5, the NFC source is corn stalk powder, the essential oil is orange peel essential oil, the lubricant is a 1:1 mixture of stearic acid and ethylene bisstearamide, the stabilizer is antioxidant 1010, and the surfactant is Tween-80.

[0043] Table 1

[0044] Serial number serial number PPC NCS NFC Essential Oils Lubricants Stabilizer Surfactants Shearing time / h Example 1 C1 100 8 0 5 0.5 1 0.5 2 Example 2 C2 100 8 2 5 0.5 1 0.5 2 Example 3 C3 100 8 6 5 0.5 1 0.5 2 Example 4 C4 100 8 10 5 0.5 1 0.5 2 Example 5 C5 100 8 14 5 0.5 1 0.5 2

[0045] The method for preparing the PPC / NCS / NFC composite film of Example 1 comprises the following steps:

[0046] 1. One-pot preparation of NFC and NCS

[0047] 1) 14 parts of corn stalk powder were mixed with 90 parts of 20 wt% sodium hydroxide solution, stirred in a water bath at 75° C. for 6 h, filtered after the reaction was completed, washed the solid sample obtained by filtration until neutral, added a mixed solution of 90 parts of 15 wt% sodium chlorite solution and 4 parts of glacial acetic acid, heated and stirred at 80° C. for 2 h, then washed with pure water until neutral, and dried to absolute dryness;

[0048] 2) 0 parts of the dried sample obtained in 1) and 8 parts of CS were placed in a container, and pure water was added to adjust the solid-liquid ratio to 1:15, and then the solid-liquid mixture was placed in a homogenizer for high-speed shearing at a speed of 16000 rpm for 2 hours. Finally, a centrifuge with a speed of 12000 rpm was used for centrifugation for 5 minutes, and a mixed powder of NFC and NCS was obtained after freeze drying.

[0049] 2. Preparation of PPC / NCS / NFC composite film

[0050] a: First, add 5 parts of orange peel essential oil to the mixed powder of NFC and NCS obtained in step 2) above, then add 0.5 parts of surfactant, blend in a high-speed mixer for 40 minutes, then add 100 parts of PPC, 0.5 parts of lubricant, and 1 part of stabilizer and continue blending for 60 minutes.

[0051] b: melt-extrude the mixture obtained in step a into a twin-screw extruder for granulation at a temperature of 180° C. and a screw speed of 120 rpm to obtain PPC / NCS / NFC composite particles;

[0052] c: The composite particles obtained in step b are processed into a PPC / NCS / NFC composite film using a flat vulcanizer, the pre-pressing pressure of the flat vulcanizer is 0.5 MPa, the pre-pressing time is 180 s, the pressing pressure is 2.5 MPa, the pressing time is 150 s, and the hot pressing temperature is 150°C.

[0053] The thickness of the composite film is about 0.31 mm.

[0054] The preparation methods of the PPC / NCS / NFC composite films of Examples 2 to 5 are basically the same as those of Example 1, except that, in the preparation step 2) of Examples 2 to 5, the mass fractions of the dried sample obtained in 1) are 2 parts, 6 parts, 10 parts, and 14 parts, respectively, to prepare the PPC / NCS / NFC composite films of Examples 2 to 5, respectively.

[0055] For the PPC / NCS / NFC composite films of Examples 1 to 5, a cutter was used to process them into tensile test samples. The mechanical properties of the PPC / NCS / NFC composite films of Examples 1 to 5 were grouped and tested according to the method of national standard GB / T1040.1-2018. The tensile test sample is a dumbbell-shaped specimen with a length of 50 mm, a gauge length of 30 mm, a middle width of 4 mm, and a thickness of approximately 0.31 mm. The stretching speed is 20 mm / min. At least 5 specimens are tested in each group. The average values ​​of the tensile strength, tensile modulus, and tensile elongation at break of the samples are taken. The results are as follows: Figure 1 shown.

[0056] from Figure 1It can be seen that after adding NFC, the tensile strength and elastic modulus of the PPC / NCS / NFC composite film showed an upward trend, and the tensile strength and elastic modulus of all composite films were higher than those of the sample with 0 NFC addition (C1). Compared with C1, the tensile strength of C4 increased from 9.80MPa to 15.03MPa, an increase of 53%; the elastic modulus increased from 2.82MPa to 4.25MPa, an increase of 51%. This improvement is mainly attributed to the interfacial entanglement between NFC and PPC molecular chains. NFC has a nanofibril structure and can produce mechanical chains with PPC molecular chains. Generally, NFC plays a role in restricting the movement of PPC molecular chains in composite materials and effectively forming a network structure, thereby significantly enhancing the mechanical properties of the composite materials. In addition, all PPC composite films (C1~C5) showed excellent ductility, with a tensile fracture strain of more than 400%, which is mainly attributed to the flexibility of PPC.

[0057] The PPC / NCS / NFC composite films of Examples 1 to 5 were quenched with liquid nitrogen and observed at a magnification of 10,000 times at 3 kV. Figure 2 The scanning electron microscope images of the fracture surface of the PPC / NCS / NFC composite film are shown. The fracture surface of the film without NFC (C1) shows a certain wrinkle structure, indicating that the composite material has a tough fracture characteristic. With the increase of NFC content, white stripes appear in the SEM image. These white stripes are NFC at the cross section at the time of fracture. They are well embedded in the matrix and improve the mechanical properties of the composite material. The network structure formed by NFC and PPC matrix can be observed in C5, which is conducive to mechanical interlocking with polymer molecules. In all SEM observations, no micron-scale agglomerates of NFC were observed, which also shows that the good dispersion of NFC and the formation of network structure are important for enhancing the mechanical properties of the composite material. And this is consistent with the improvement of mechanical properties observed in the tensile test.

[0058] The PPC / NCS / NFC composite films of Examples 1 to 5 were completely folded to 0° using external force at 25°C and kept in the folded state for 1 minute. After the external force was removed, the angles formed by the composites increased until their angles remained unchanged. The angles formed by the composites at different times were recorded to analyze the recovery rates of different groups. The results are shown in Table 1. Figure 3As shown. According to the observation, the recovery angle of the composite material containing NFC is significantly better than that of C1 within the same recovery time. Specifically, when the recovery time is 3s, the recovery angle of the former is 105°, while that of the latter is greater than 130°, and with the gradual increase in the proportion of NFC, the recovery angle and dimensional stability of the PPC composite material are enhanced. Among them, C5 has the best dimensional stability, with a recovery angle of 138° at 3s, 168° at 30s, 170° at 1min, and 173° at 5min. This improvement is attributed to the nanofiber structure of NFC, which wraps the molecular chain of PPC and can support the extension of the PPC molecular chain.

[0059] The mass fraction compositions of the PPC / NCS / NFC composite films of Examples 6 to 10 are shown in Table 2, and the PPC / NCS / NFC composite films of Examples 6 to 10 are numbered S1, S2, S3, S4, and S5, respectively, for single factor experiments.

[0060] In Examples 6 to 10, the NFC source is bamboo powder, the lubricant is a 1:1 mixture of oleamide and erucamide, the stabilizer is antioxidant 1076, and the surfactant is Tween-85.

[0061] Table 2

[0062] Serial number serial number PPC NCS NFC Essential Oils Lubricants Stabilizer Surfactants Shearing time / h Example 6 S1 100 0 14 0 0.5 0.5 0.5 2 Example 7 S2 100 2 14 0 0.5 0.5 0.5 2 Example 8 S3 100 5 14 0 0.5 0.5 0.5 2 Example 9 S4 100 7 14 0 0.5 0.5 0.5 2 Example 10 S5 100 10 14 0 0.5 0.5 0.5 2

[0063] The method for preparing the PPC / NCS / NFC composite film of Example 6 comprises the following steps:

[0064] 1. One-pot preparation of NFC and NCS

[0065] 1) 20 parts of bamboo powder were mixed with 85 parts of 20 wt% sodium hydroxide solution, stirred in a water bath at 75° C. for 6 h, filtered after the reaction was completed, washed the solid sample obtained by filtration until it was neutral, added with a mixed solution of 85 parts of 15 wt% sodium chlorite solution and 4 parts of glacial acetic acid, heated and stirred at 70° C. for 2 h, then washed with pure water until it was neutral, and dried to absolute dryness;

[0066] 2) 14 parts of the dried sample obtained in 1) and 0 parts of CS were placed in a container, and pure water was added to adjust the solid-liquid ratio to 1:10, and then the solid-liquid mixture was placed in a homogenizer for high-speed shearing at a speed of 10,000 rpm for 2 hours. Finally, a centrifuge with a speed of 10,000 rpm was used for centrifugation for 3 minutes, and a mixed powder of NFC and NCS was obtained after freeze drying.

[0067] 2. Preparation of PPC / NCS / NFC composite film

[0068] a: First, add 0 parts of essential oil to the mixed powder of NFC and NCS obtained in step 2) above, then add 0.5 parts of surfactant, blend in a high-speed mixer for 20 minutes, then add 100 parts of PPC, 0.5 parts of lubricant, and 0.5 parts of stabilizer and continue blending for 30 minutes.

[0069] b: melt-extrude the mixture obtained in step a in a twin-screw extruder for granulation at a temperature of 150° C. and a screw speed of 100 rpm to obtain PPC / NCS / NFC composite particles;

[0070] c: Process the composite particles obtained in step b into a PPC / NCS / NFC composite film using a flat vulcanizer. The pre-pressing pressure of the flat vulcanizer is 0.5 MPa, the pre-pressing time is 150 s, the pressing pressure is 2.5 MPa, the pressing time is 150 s, and the hot pressing temperature is 140°C.

[0071] The thickness of the composite film is about 0.30 mm.

[0072] The preparation methods of the PPC / NCS / NFC composite films of Examples 7 to 10 are basically the same as those of Example 6, except that in the preparation step 2) of Examples 7 to 10, the mass fractions of CS are 2 parts, 5 parts, 7 parts, and 10 parts, respectively, to prepare the PPC / NCS / NFC composite films of Examples 7 to 10, respectively.

[0073] For the PPC / NCS / NFC composite films of Examples 6 to 10, a cutter was used to process them into antibacterial test samples. The antibacterial properties of the PPC / NCS / NFC composite films of Examples 6 to 10 were grouped and tested according to the method of national standard GB / T 31402-2015. The tensile test sample was a circular specimen with a sample diameter of 50 mm and a thickness of 3 mm. It was incubated with Escherichia coli and Staphylococcus aureus suspensions in a water bath oscillator at 160 rpm at 36 ± 1 ° C for 60 min. A group of samples without composite materials were taken as the control group. 100 μL of solution was diluted to 105 CFU / mL. Then, 500 μL of the diluted bacterial solution was applied to a culture dish containing LB broth (pH = 7) agar using an L-shaped rod. The culture dish was incubated at 37 ° C for 48 h. After 48 h, the bacterial growth state was observed and the number of colonies was counted.

[0074] Antibacterial activity of PPC / NCS / NFC composite film against Escherichia coli Figure 4 As shown in Figure 2, the antibacterial properties against Staphylococcus aureus are Figure 5As shown. By observing the samples cultured for 48 hours, it was found that the composite film (S1) with only PPC and NFC added had almost no inhibitory effect on Escherichia coli and Staphylococcus aureus. The composite films with 7 and 10 parts of NCS showed similar antibacterial ability, which was much stronger than the other groups. In addition, the composite films with NCS added (S2-S5) had a greater inhibitory effect on Staphylococcus aureus than on Escherichia coli. This is because the inhibitory effect of NCS on Gram-positive bacteria (Staphylococcus aureus) is greater than that on Gram-negative bacteria (Escherichia coli). There are a large number of amino groups on the surface of NCS, among which the positively charged –NH 3+ The groups are more likely to bind to the negatively charged membranes of Gram-positive pathogens, and there is an electrostatic interaction between NCS and the bacterial cell wall. In this sense, because the cell wall of Gram-positive microorganisms is composed of a thick peptidoglycan layer and a polymer called teichoic acid, this teichoic acid skeleton is highly charged by negatively charged phosphate groups, which can establish electrostatic interactions with cationic antimicrobial compounds such as NCS. Therefore, Gram-positive microorganisms are more easily affected than Gram-negative microorganisms, and therefore exhibit better antibacterial properties.

[0075] The mass fraction compositions of the PPC / NCS / NFC composite films of Examples 11 to 15 are shown in Table 3, and the PPC / NCS / NFC composite films of Examples 11 to 15 are numbered K1, K2, K3, K4, and K5, respectively, for single factor experiments.

[0076] In Examples 11 to 15, the NFC source is rice straw powder, the essential oil is wormwood essential oil, the lubricant is a 1:2:1 mixture of ethylene bisstearamide, oleamide, and erucamide, the stabilizer is antioxidant 1076, and the surfactant is mannitol erythritol lipid-a.

[0077] Table 3

[0078] Serial number serial number PPC NCS NFC Essential Oils Lubricants Stabilizer Surfactants Shearing time / h Embodiment 11 K1 100 7 14 0 0.5 0.5 0.5 2 Example 12 K2 100 7 14 2 0.5 0.5 0.5 2 Example 13 K3 100 7 14 5 0.5 0.5 0.5 2 Embodiment 14 K4 100 7 14 7 0.5 0.5 0.5 2 Embodiment 15 K5 100 7 14 10 0.5 0.5 0.5 2

[0079] The method for preparing the PPC / NCS / NFC composite film of Example 11 comprises the following steps:

[0080] 1. One-pot preparation of NFC and NCS

[0081] 1) 25 parts of rice straw powder were mixed with 90 parts of 20 wt% sodium hydroxide solution, stirred in a water bath at 75° C. for 6 h, filtered after the reaction was completed, washed the solid sample obtained by filtration until neutral, added a mixed solution of 85 parts of 15 wt% sodium chlorite solution and 5 parts of glacial acetic acid, heated and stirred at 80° C. for 2 h, then washed with pure water until neutral, and dried to absolute dryness;

[0082] 2) 14 portions of the dried sample obtained in 1) and 7 portions of CS were placed in a container, and pure water was added to adjust the solid-liquid ratio to 1:20, and then the solid-liquid mixture was placed in a homogenizer for high-speed shearing at a speed of 13,000 rpm for 2 hours. Finally, a centrifuge with a speed of 15,000 rpm was used for centrifugation for 3 minutes, and a mixed powder of NFC and NCS was obtained after freeze drying.

[0083] 2. Preparation of PPC / NCS / NFC composite film

[0084] a: First, add 0 parts of wormwood essential oil to the mixed powder of NFC and NCS obtained in the above step 2), then add 0.5 parts of surfactant, blend in a high-speed mixer for 30 minutes, then add 100 parts of PPC, 0.5 parts of lubricant, and 0.5 parts of stabilizer and continue blending for 50 minutes.

[0085] b: melt-extrude the mixture obtained in step a into a twin-screw extruder for granulation at a temperature of 160° C. and a screw speed of 120 rpm to obtain PPC / NCS / NFC composite particles;

[0086] c: The composite particles obtained in step b are processed into a PPC / NCS / NFC composite film using a flat vulcanizer. The pre-pressing pressure of the flat vulcanizer is 0.7 MPa, the pre-pressing time is 180 s, the pressing pressure is 3.5 MPa, the pressing time is 180 s, and the hot pressing temperature is 150°C.

[0087] The thickness of the composite film is about 0.33 mm.

[0088] The preparation method of the PPC / NCS / NFC composite film of Example 12 to Example 15 is basically the same as that of Example 11, except that in the preparation step a of Example 12 to Example 15, the mass fraction of wormwood essential oil is 2 parts, 5 parts, 7 parts, and 10 parts, respectively, to prepare the PPC / NCS / NFC composite films of Example 12 to Example 15, respectively.

[0089] For the PPC / NCS / NFC composite films of Examples 11 to 15, a cutter was used to process them into antibacterial test samples. The antibacterial properties of the PPC / NCS / NFC composite films of Examples 11 to 15 were grouped and tested according to the method of national standard GB / T 31402-2015. The tensile test sample was a circular specimen with a sample diameter of 50 mm and a thickness of 3 mm. It was incubated with Escherichia coli and Staphylococcus aureus suspensions at 160 rpm at 36 ± 1 ° C for 60 min in a water bath oscillator. A group of samples without composite materials were taken as the control group. 100 μL of solution was diluted to 105 CFU / mL. Then, 500 μL of the diluted bacterial solution was applied to a culture dish containing LB broth (pH = 7) agar using an L-shaped rod. The culture dish was incubated at 37 ° C for 48 h. After 48 h, the bacterial growth state was observed and the number of colonies was counted.

[0090] Antibacterial activity of PPC / NCS / NFC composite film against Escherichia coli Figure 6 As shown in Figure 2, the antibacterial properties against Staphylococcus aureus are Figure 7 As shown. By observing the samples cultured for 48 hours, it is known that the composite films (K2~K5) with the addition of essential oils show better antibacterial properties than the composite films (K1 and S1~S5) without the addition of essential oils, and they show synergistic antibacterial effects. This is because NCS is positively charged and can interact electrostatically with negatively charged essential oils, and the hydrophobic essential oils can improve the hydrophilic properties of chitosan and improve the reaction performance of chitosan. Among them, the composite film (K3) with 5 parts of essential oil added has the strongest inhibitory effect on Escherichia coli and Staphylococcus aureus. This is because too much essential oil will not be able to fully electrostatically bind with CS, thereby reducing their synergistic effect. The composite films (K2-K5) with additional essential oils have a greater inhibitory effect on Staphylococcus aureus than on Escherichia coli. This is because Gram-positive bacteria (Staphylococcus aureus) are more easily inhibited by essential oils than Gram-negative bacteria (Escherichia coli). This is because Gram-negative bacteria have hydrophilic lipopolysaccharide protection on their outer membrane, which reduces their sensitivity to essential oils, thereby preventing essential oils from entering and destroying bacterial cells.

[0091] The mass fraction compositions of the PPC / NCS / NFC composite films of Examples 16 and 17 are shown in Table 4, and the PPC / NCS / NFC composite films of Examples 16 and 17 are respectively denoted by numbers F1 and F2 for single factor experiments.

[0092] In Examples 16 and 17, the NFC source is wood powder, the essential oil is cinnamon essential oil, the lubricant is a 2:1:1 mixture of ethylene bisstearamide, oleamide, and erucamide, the stabilizer is antioxidant 1010, and the surfactant is mannitol erythritol lipid-b.

[0093] Table 4

[0094] Serial number serial number PPC NCS NFC Essential Oils Lubricants Stabilizer Surfactants Shearing time / h Example 16 F1 100 7 2 5 0.5 0.5 1 0.5 Embodiment 17 F2 100 7 2 5 0.5 0.5 1 2

[0095] The method for preparing the PPC / NCS / NFC composite film of Example 16 comprises the following steps:

[0096] 1. One-pot preparation of NFC and NCS

[0097] 1) 20 parts of wood powder were mixed with 70 parts of 10 wt% sodium hydroxide solution, stirred in a water bath at 75° C. for 6 h, filtered after the reaction was completed, washed the solid sample obtained by filtration until it was neutral, added with a mixed solution of 80 parts of 10 wt% sodium chlorite solution and 4 parts of glacial acetic acid, heated and stirred at 70° C. for 1 h, then washed with pure water until it was neutral, and dried to absolute dryness;

[0098] 2) 2 portions of the dried sample obtained in 1) and 7 portions of CS were placed in a container, and pure water was added to adjust the solid-liquid ratio to 1:15, and then the solid-liquid mixture was placed in a homogenizer for high-speed shearing at a speed of 11000 rpm for 0.5 h. Finally, a centrifuge with a speed of 12000 rpm was used for centrifugation for 3 min, and a mixed powder of NFC and NCS was obtained after freeze drying.

[0099] 2. Preparation of PPC / NCS / NFC composite film

[0100] a: First, add 5 parts of cinnamon essential oil to the mixed powder of NFC and NCS obtained in step 2) above, then add 1 part of surfactant, blend in a high-speed mixer for 30 minutes, then add 100 parts of PPC, 0.5 parts of lubricant, and 0.5 parts of stabilizer and continue blending for 40 minutes.

[0101] b: melt-extrude the mixture obtained in step a into a twin-screw extruder for granulation at a temperature of 180° C. and a screw speed of 160 rpm to obtain PPC / NCS / NFC composite particles;

[0102] c: The composite particles obtained in step b are processed into a PPC / NCS / NFC composite film using a flat vulcanizer. The pre-pressing pressure of the flat vulcanizer is 0.7 MPa, the pre-pressing time is 180 s, the pressing pressure is 3.5 MPa, the pressing time is 180 s, and the hot pressing temperature is 150°C.

[0103] The thickness of the composite film is about 0.30 mm.

[0104] The preparation method of the PPC / NCS / NFC composite film of Example 17 is basically the same as that of Example 16, except that in the preparation step 2) of Example 17, the shearing time of the homogenizer is 2 hours.

[0105] For the PPC / NCS / NFC composite films of Examples 16 to 17, a cutter was used to process them into tensile test samples. The mechanical properties of the PPC / NCS / NFC composite films of Examples 16 to 17 were grouped and tested according to the method of national standard GB / T1040.1-2018. The tensile test sample is a dumbbell-shaped specimen with a length of 50 mm, a gauge length of 30 mm, a middle width of 4 mm, and a thickness of approximately 0.30 mm. The stretching speed is 20 mm / min. At least 5 specimens are tested in each group. The average values ​​of the tensile strength, tensile modulus, and tensile elongation at break of the samples are taken. The results are as follows: Figure 8 shown.

[0106] Compared with the sample F1 which was sheared for a short time, F2 showed better mechanical properties after shearing for 2h. Specifically, the tensile strength increased from 8.01MPa to 11.25MPa, an increase of 40.4%, and the elastic modulus increased from 2.32MPa to 3.38MPa, an increase of 45.3%. This improvement can be attributed to the fact that the shear force transforms both cellulose and CS into nanoscale. The molecular structures of NFC and NCS are very similar, so NFC and NCS have good compatibility and stronger performance. At the same time, under high-speed shearing, NFC and NCS are evenly mixed, and bridging hydrogen bonds are formed between the highly dispersed NFC and NCS, thereby improving the film performance. In contrast, due to the short shearing time of F1, neither cellulose nor CS was fully sheared, which explains why the tensile strength of F1 is lower than that of F2.

[0107] The PPC / NCS / NFC composite films of Examples 16 and 17 were quenched with liquid nitrogen and observed at 3 kV with a magnification of 10,000 times. Fig. 9 The SEM images of the fractured surfaces of the PPC / NCS / NFC composite films are shown. Fig. 9 The PPC / NCS / NFC composite film of a exhibits an inhomogeneous phase structure, and granular fillers with larger particle sizes can be seen, which indicates that the NFC and NCS in the sample with insufficient shearing are unevenly distributed in the matrix, which reduces the compatibility of PPC, NFC and NCS, and the larger particle size also leads to larger voids, which is the main reason for the low mechanical properties. Fig. 9 b, The particle size and voids of NFC and NCS are reduced, which leads to the improvement of the mechanical properties of the samples.

[0108] The mass fraction compositions of the PPC / NCS / NFC composite films of Examples 18 to 22 are shown in Table 5, and the PPC / NCS / NFC composite films of Examples 18 to 22 are numbered H1, H2, H3, H4, and H5, respectively, for single factor experiments.

[0109] In Examples 18 to 22, the NFC source is cotton stalk powder, the essential oil is hyssop essential oil, the lubricant is a mixture of ethylene bisstearamide, oleamide, and erucamide in a ratio of 1:1:2, the stabilizer is antioxidant 1790, and the surfactant is Tween-80.

[0110] Table 5

[0111] Serial number serial number PPC NCS NFC Essential Oils Lubricants Stabilizer Surfactants Shear speed / rpm Embodiment 18 H1 100 7 14 5 1 0.5 0.5 10000 Embodiment 19 H2 100 7 14 5 1 0.5 0.5 12000 Embodiment 20 H3 100 7 14 5 1 0.5 0.5 14000 Embodiment 21 H4 100 7 14 5 1 0.5 0.5 16000 Embodiment 22 H5 100 7 14 5 1 0.5 0.5 18000

[0112] The method for preparing the PPC / NCS / NFC composite film of Example 18 comprises the following steps:

[0113] 1. One-pot preparation of NFC and NCS

[0114] 1) 25 parts of cotton stalk powder were mixed with 80 parts of 20 wt% sodium hydroxide solution, stirred in a water bath at 75° C. for 6 h, filtered after the reaction was completed, washed the solid sample obtained by filtration until it was neutral, added with a mixed solution of 90 parts of 15 wt% sodium chlorite solution and 5 parts of glacial acetic acid, heated and stirred at 80° C. for 2 h, then washed with pure water until it was neutral, and dried to absolute dryness;

[0115] 2) 14 portions of the dried sample obtained in 1) and 7 portions of CS were placed in a container, and pure water was added to adjust the solid-liquid ratio to 1:20, and then the solid-liquid mixture was placed in a homogenizer for high-speed shearing at a speed of 10,000 rpm for 2 hours. Finally, a centrifuge with a speed of 15,000 rpm was used for centrifugation for 3 minutes, and a mixed powder of NFC and NCS was obtained after freeze drying.

[0116] 2. Preparation of PPC / NCS / NFC composite film

[0117] a: First, add 5 parts of hyssop essential oil to the mixed powder of NFC and NCS obtained in the above step 2), then add 0.5 parts of surfactant, blend in a high-speed mixer for 30 minutes, then add 100 parts of PPC, 1 part of lubricant, and 0.5 parts of stabilizer and continue blending for 30 minutes.

[0118] b: The mixture obtained in step a was melt-extruded and granulated in a twin-screw extruder at a temperature of 180°C and a screw speed of 160

[0119] rpm, and PPC / NCS / NFC composite particles were obtained;

[0120] c: Process the composite particles obtained in step b into a PPC / NCS / NFC composite film using a flat vulcanizer. The pre-pressing pressure of the flat vulcanizer is 0.7 MPa, the pre-pressing time is 180 s, the pressing pressure is 3.5 MPa, the pressing time is 180 s, and the hot pressing temperature is 140°C.

[0121] The thickness of the composite film is about 0.29 mm.

[0122] The preparation method of the PPC / NCS / NFC composite film of Examples 19 to 22 is basically the same as that of Example 18, except that in the preparation step 2) of Examples 19 to 22, the homogenization speed is 12000 rpm, 14000 rpm, 16000 rpm, and 18000 rpm, respectively.

[0123] For the PPC / NCS / NFC composite films of Examples 19 to 22, a cutter was used to process them into tensile test samples. The mechanical properties of the PPC / NCS / NFC composite films of Examples 19 to 22 were grouped and tested according to the method of national standard GB / T1040.1-2018. The tensile test sample is a dumbbell-shaped specimen with a length of 50 mm, a gauge length of 30 mm, a middle width of 4 mm, and a thickness of approximately 0.29 mm. The stretching speed is 20 mm / min. At least 5 specimens are tested in each group. The average values ​​of the tensile strength, tensile modulus, and tensile elongation at break of the samples are taken. The results are as follows: Fig.10 shown.

[0124] from Fig.10 It can be seen that the shear rate improves the tensile strength and elastic modulus of the PPC / NCS / NFC composite film, and the maximum value is reached when the rotation speed is 16000rpm (H3). Specifically, the tensile strength increases from 13.12MPa to 16.53MPa, an increase of 26.1%, and the elastic modulus increases from 3.73MPa to 5.74MPa, an increase of 53.9%. These results confirm that the shear rate has a significant improvement effect on the mechanical properties of the PPC / NCS / NFC composite film. The reason may be that with the increase of the shear rate, the cellulose and CS particles are subjected to greater mechanical and frictional forces, making the particles gradually become smaller. Fine particles have a larger surface area, which can increase the contact area between the material and other components, improve the interfacial bonding strength, and also reduce voids and internal defects. This improves the uniformity of the dispersion of nanoparticles in the composite material. The uniform dispersion of nanoparticles is conducive to improving the mechanical properties of the material and improving the density and tightness of the material. However, when the shear rate reached 18000rpm, the mechanical properties of the PPC / NCS / NFC composite film decreased. The reason may be that the high-speed shear caused violent collision and friction between the particles, resulting in excessive wear and even peeling of the particle surface, which in turn caused the particles to deform or even break.

Claims

1. A polypropylene carbonate (PPC) / nano chitosan (NCS) / nano cellulose (NFC) composite film, characterized in that: The mass ratio of the composition is: 100 parts of PPC, 1-10 parts of NCS, 1-14 parts of NFC, 1-10 parts of essential oil, 0.5-1 parts of lubricant, 0.5-1 parts of stabilizer, and 0.5-1 parts of surfactant. The lubricant is one or a combination of two or more of stearic acid, ethylene bis stearic acid amide, oleic acid amide, and erucic acid amide; the stabilizer is one or a combination of two or more of antioxidant 1010, antioxidant 168, antioxidant 1076, and antioxidant 1790; the surfactant is one or a combination of two or more of Tween-80, Tween-85, mannitol erythritol lipid-a, and mannitol erythritol lipid-b. The preparation method of the PPC / NCS / NFC composite film comprises the following steps: 1) 10 to 30 parts of biomass powder are mixed with 70 to 90 parts of sodium hydroxide solution, stirred in a water bath at 75° C. for 6 hours, filtered after the reaction is completed, washed the solid sample obtained by filtration until neutral, added with a mixed solution of 80 to 90 parts of sodium chlorite solution and 4 to 5 parts of glacial acetic acid, heated and stirred at 70 to 80° C. for 1 to 2 hours, then washed with pure water until neutral, and dried to absolute dryness; 2) 1 to 14 parts of the dried sample obtained in step 1) and 1 to 10 parts of chitosan (CS) are placed in a container, pure water is added to adjust the solid-liquid ratio to 1:10 to 1:20, and then the solid-liquid mixture is placed in a homogenizer at a speed of 10,000 to 18,000 rpm for high-speed shearing for 0.5 to 2 hours. Finally, a centrifuge with a speed of 10,000 to 15,000 rpm is used for centrifugation for 3 to 5 minutes, and a mixed powder of NFC and NCS is obtained after freeze drying. 3) First, 1 to 10 parts of essential oil are added to the mixed powder of NFC and NCS obtained in step 2), and then 0.5 to 1 part of surfactant is added, and the mixture is blended in a high-speed mixer for 20 to 40 minutes, and then 100 parts of PPC, 0.5 to 1 part of lubricant, and 0.5 to 1 part of stabilizer are added and the mixture is blended for 30 to 60 minutes. 4) melt-extrude the mixture obtained in step 3) in a twin-screw extruder for granulation at a temperature of 110 to 180° C. and a screw speed of 60 to 200 rpm to obtain PPC / NCS / NFC composite particles; 5) The composite particles obtained in step 4) are processed into a PPC / NCS / NFC composite film using a flat vulcanizer, a blown film machine or a cast film machine.

2. A PPC / NCS / NFC composite film according to claim 1, characterized in that: The nanocellulose is sourced from one or a combination of two or more of wood powder, bamboo powder, corn straw powder, rice straw powder and cotton stalk powder in biomass powder.

3. A PPC / NCS / NFC composite film according to claim 1, characterized in that: The mesh size of biomass powder is 80-150 mesh.

4. A PPC / NCS / NFC composite film according to claim 1, characterized in that: In step 5), the pre-pressing pressure of the flat vulcanizer is 0.5-0.7 MPa, the pre-pressing time is 150-180 s, the pressing pressure is 2.5-3.5 MPa, the pressing time is 150-180 s, and the hot pressing temperature is 140-150° C. The processing temperature of the film blowing machine is 120-160° C. The processing temperature of the cast film machine is 120-160° C.

5. A PPC / NCS / NFC composite film according to claim 1, characterized in that: In step 5), the thickness of the PPC / NCS / NFC composite film is 0.05 mm to 0.8 mm.

Citation Information

Patent Citations

  • Novel edible antibacterial food packaging film and preparation method thereof

    CN106750580A

  • Degradable packaging film with antibacterial function and preparation method thereof

    CN108410151A

  • Biodegradable film raw material composition and biodegradable film material

    CN111748180A

  • Fresh-keeping packaging film and preparation method thereof

    CN116041829A

  • New biodegradative composite material and its production

    JP1992059830A

Cited By

  • Glass fiber reinforced polypropylene material for blow molding and preparation method thereof

    CN121406051A